Isopoda (Crustacea) do complexo estuarino-lagunar Mundaú/Manguaba, Alagoas, Brasil - Loyola e Silva,Jayme de (1994)
Qualilative and quantitative studies of Isopoda species were made at Mundaú/Manguaba Estuary-Lagoon Complex on the Coast of Alagoas State. Six points were established in order to carry out methodical collections of animals. These collections were made monthly, without interruption, from April, 1990 to March, 1991, in which three families, five genera and seven species of Isopoda were identified. A special key for identification of Isopoda and also diagnosis for each species are presented. Sphaeromatidae Family was the most significant and Cassidinidea fluminensis (Mane-Garzón, 1944), was the species with numerical dominance. Space/time distribution of the species of Isopoda was related to the variation of salinity.